USERS BEHAVIOR MODEL IN TASKS OF COMPUTER SYSTEMS SECURITY ANALYSIS - Shyrochin, V. P.; Mukhin, V. E.; Bing, Hu Zheng (International Journal of Computing, 2014)
Security of computer systems of various purpose and the appropriate information technologies appreciably depends on tools of user identification and authentication, and also on tools of the analysis of their behavior and behavior of their programs during reception of access to those or other information resources. This article is devoted to a substantiation of a method of use of a known formalism - state machine for modeling users behavior and to testing of protection tools on detection of attempts of the non-authorized access to information resources, including at early stages of preparation for such actions.